The Association of Abnormal Liver Tests with Hepatitis C Testing in Primary Care - Schreiner, Andrew D. (Am J Med, 2019)
BACKGROUND: As hepatitis C virus birth cohort (1945–1965) screening in primary care improves, testing patterns in response to persistently abnormal liver tests are less well known. METHODS: This retrospective cohort study of a patient-centered medical home between 2007 and 2016 evaluates the association of abnormal liver chemistries and other clinical and demographic factors with Hepatitis C antibody (HCV Ab) testing in patients with persistently abnormal liver tests. Patients with at least 2 consecutive abnormal liver tests were categorized by the clinical pattern of liver chemistry abnormality, including cholestatic, hepatocellular, and mixed patterns. The primary outcomes were: (1) completed HCV Ab tests; and (2) positive HCV Ab results for those patients tested. RESULTS: Of 4,512 patients with consecutive abnormal liver tests, only 730 (16%) underwent HCV Ab testing within 1 year of the second abnormality; 81/730 (11%) had HCV Ab detected. A logistic regression model revealed that mixed (OR, 2.20; 95% CI, 1.72–2.82) and hepatocellular (OR, 1.43; 95% CI, 1.15–1.79) patterns of liver test abnormality, female gender, alcohol and tobacco abuse were associated with higher odds of HCV Ab testing. Hepatocellular (OR, 7.51; 95% CI 2.18, 25.94) and mixed patterns (OR, 5.88; 95% CI, 1.64–21.15) of liver test abnormalities, male gender, Medicaid enrollment, and drug and tobacco abuse had higher odds of positive HCV Ab results. CONCLUSIONS: There is opportunity to improve Hepatitis C diagnostic testing in patients with consecutively elevated liver tests, and hepatocellular and mixed patterns of abnormality should prompt primary care providers to action.